Feasibility and effectiveness of an evidence-based asthma service in Australian community pharmacies: a pragmatic cluster randomised trial - Armour, Carol; Reddel, Helen; LeMay, Kate; Saini, Bandana; Smith, Lorraine; Bosnic-Anticevich, Sinthia; Song, Yun Ju; Alles, Chehani; Burton, Deborah; Emmerton, Lynne; Stewart, Kay; Krass, Ines (Informa Healthcare, 2013)
Objective: To test the feasibility, effectiveness and sustainability of a pharmacy asthma service in primary care. Methods: A pragmatic cluster randomised trial in community pharmacies in four Australian states/territories in 2009. Specially trained pharmacists were randomised to deliver an asthma service in two groups, providing 3 or 4 consultations over 6 months. People with poorly-controlled asthma or no recent asthma review were included. Follow-up for 12 months after service completion occurred in 30% of randomly-selected completing patients. Outcomes included change in asthma control (poor, fair/good) and Asthma Control Questionnaire (ACQ) score, inhaler technique, quality of life, perceived control, adherence, asthma knowledge and asthma action plan ownership. Objective: To test the feasibility, effectiveness and sustainability of a pharmacy asthma service in primary care. Methods: A pragmatic cluster randomised trial in community pharmacies in four Australian states/territories in 2009. Specially trained pharmacists were randomised to deliver an asthma service in two groups, providing 3 or 4 consultations over 6 months. People with poorly-controlled asthma or no recent asthma review were included. Follow-up for 12 months after service completion occurred in 30% of randomly-selected completing patients. Outcomes included change in asthma control (poor, fair/good) and Asthma Control Questionnaire (ACQ) score, inhaler technique, quality of life, perceived control, adherence, asthma knowledge and asthma action plan ownership. Conclusions: The pharmacy asthma service delivered clinically important improvements in both a 3-visit and 4-visit service. Pharmacists were able to recruit and deliver the service with minimal intervention suggesting it is practical to implement in practice. The 3-visit service would be feasible and effective to implement, with a review at 12 months.